Social Networks as Public Relations Tools in European Institutions - Baamonde Silva, Xosé (2011)
Internet is the digital agora in where that all can participate. The European institutions can use the social networks like tools of dialogue with the citizens to attain his implication and commitment with the process of European construction. This investigation analyses the spaces in Internet of the main entities of the EU to check if they are using the new technological potentialities to converse directly with the citizenship or still keep a special attention to the media like intermediaries to transmit their messages to the public opinion.